Study on portable haptic guide device with omnidirectional driving gear. (4th March 2021) - Aizawa, Tetsuya; Iizima, Haruhiko; Abe, Kazuki; Tadakuma, Kenjiro; Tadakuma, Riichiro
Abstract : In the past, white canes, guide dogs, and guide helpers have served to assist visually impaired people when walking outdoors. However, these assistance methods have various limitations for extended and suitable usage. Therefore, our laboratory herein proposes a route guidance device that signals commands to the end-user by giving a sense of force to the thumb. The guide device is driven on the common plane with two degrees of freedom by using an XY stage with omnidirectional driving gear. The current prototype presents challenges for its practical implementation as a smooth, safe and reliable route guidance system. In this study, we conducted experiments aiming to optimize the combination of the update position of the intermediate target point and the presentation cycle in blindfolded clear-eyed people. GRAPHICAL ABSTRACT: UF0001